1993
DOI: 10.1159/000261586
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Dental Caries in a Population of Spanish Schoolchildren with Low Levels of Caries Experience

Abstract: The aim of this study was to analyze the relationship between current dietary habits and dental caries in schoolchildren from an area of Spain on which the prevalence of caries was low. The results of an epidemiological study conducted on a random sample of 893 children from the cities of Girona and Figueres are presented. The method of dietary interview consisted of a food-frequency questionnaire. This showed a positive relationship between dental caries and consumption of ice cream, pastries, cakes, sliced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…The importance of diet in caries incidence has, however, been demonstrated in other studies, with regard to total amount consumed 22 , as well as the frequency of intake 3,31,32,59 . It should be noted that the correlation between diet and caries prevalence will be low when caries prevalence is low and the difference in diet habits is small.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The importance of diet in caries incidence has, however, been demonstrated in other studies, with regard to total amount consumed 22 , as well as the frequency of intake 3,31,32,59 . It should be noted that the correlation between diet and caries prevalence will be low when caries prevalence is low and the difference in diet habits is small.…”
Section: Discussionmentioning
confidence: 89%
“…No study, however, has used a semiquantitative food frequency questionnaire covering the overall general dietary intake of the study population, although a food frequency questionnaire with limited selected food items has been used 3 . According to Willett 52 , food frequency questionnaires have now become the primary method for measuring dietary intake in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the development of carious lesions and dietetic factors has been investigated since the 1940s. It has been suggested that the relationship between sugar intake and the development of carious lesions is currently different from that documented in the past decades, since dental health has improved greatly in the developed countries, with no parallel decrease in the consumption of sugar and cariogenic foods 64 .…”
Section: Discussionmentioning
confidence: 97%
“…Like for example, the intake of sugar plays a very significant role in dental caries (Gustaffson et al 1954, Nizel and Papas,1989; Rugg-Gunn 1989) was confirmed long back. But several procedural imperfections built in these studies make it hard to confirm a convinced association between dietary habits and dental caries (Screenby, 1975; Newbrun, 1982) [ 11 ]. But its role cannot be taken trivially from the recent studies [ 12 ] [ 13 ] where it is proved that dietary habits take a very important role.…”
Section: Introductionmentioning
confidence: 99%